Willingness to join in a cooperative the case of cacao seedling farmers in Brgy. Bago Oshiro, Mintal Tugbok District Davao City - Gempisaw, Christy Jean G.; Ebarle, Exegenesis Jedidiah N.
Small-scale farmers cultivate around 90% of the global cacao production. However, these farmers are marginalized with their lack of input and capital resources as well as access to technologies. In Davao City, Barangay Bago Oshiro is considered as one of the top cacao seedling producers in the region. In this study, the willingness of cacao seedling in Bago Oshiro to join in a cooperative was measured using Binary Logit Regression. A total of 52 cacao seedling farmers were interviewed and each of the farmers provided their own perspectives towards cooperatives. The study identified several factors which may affect the decision of the farmers to join in a cooperative and this include age, household size, years of education, monthly gross income, production cost, farm size, farming experience, credit access, communication with a cooperative member, participation in trainings and farmers' primary source of income. Results revealed that household size, farm size, gross income and years of education are the only statistically significant variables at a=0.05 level of significance. Household size and farm size negatively affects the farmers' decision by 0.0043 and 0.0230 respectively while gross income and years of education positively affects the decision of the farmers by 0.004283 and 0.0049 respectively. Moreover, the results revealed that an average farmer would have a 49% probability of joining in a cooperative. The study recommend that farmers should join in a cooperative to increase their farm profit and to remove the consolidators in the supply chain.
Thesis, Undergraduate(BS Agribusiness Economics)-University of the Philippines, Mindanao